2004
DOI: 10.1002/hep.20473
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S –Transferase and Liver Function in Intrahepatic Cholestasis of Pregnancy and Pruritus Gravidarum

Abstract: Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-specific liver disease associated with poor maternal and fetal outcome. The diagnosis is based on pruritus with abnormal liver function in the absence of other pathological conditions. However, pruritus in pregnancy is common, and it may be the only presenting feature in ICP. No reliable test currently exists that can discriminate between those women destined to develop ICP and those with the benign condition of pruritus gravidarum (PG). The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Impaired sulfation and abnormalities in progesterone metabolism have been found in ICP. 4 The recognition of familial cases and high incidence in certain ethnic groups have long suggested a genetic predisposition to ICP. Pedigree analysis of family members of a child with progressive familial intrahepatic cholestasis has identified a mutation in the MDR3 (ABCB4) gene associated with ICP.…”
Section: Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 99%
“…Impaired sulfation and abnormalities in progesterone metabolism have been found in ICP. 4 The recognition of familial cases and high incidence in certain ethnic groups have long suggested a genetic predisposition to ICP. Pedigree analysis of family members of a child with progressive familial intrahepatic cholestasis has identified a mutation in the MDR3 (ABCB4) gene associated with ICP.…”
Section: Intrahepatic Cholestasis Of Pregnancymentioning
confidence: 99%
“…The present study (1) identified three sulfated progesterone metabolites, 5a-pregnan-3a,-20a-diol-3,20-disulfate, 5b-pregnan-3a-20a-diol-3-sulfate, and 5b-pregnan-3a-20a-diol-3,20-disulfate, that were present in ICP patients in serum samples obtained even at [9][10][11][12][13][14][15] Abbreviations: ICP, intrahepatic cholestasis of pregnancy; PG, pruritus gravidarum.…”
mentioning
confidence: 58%
“…Patients with these characteristics have been identified in several studies, being usually labeled as having pruritus gravidarum (PG), an enigmatic entity that does not carry the fetal risks of a genuine ICP. (5,(9)(10)(11) Table 1 summarizes clinical and biochemical data previously reported in patients with ICP and in normal pregnancies, (7) comparing them with a concurrent unreported cohort of patients with PG in whom pruritus appeared at the same gestational age but was slightly less severe than in patients with ICP. In three of these patients with PG, pruritus diminished spontaneously 1 week prior to delivery; and in another patient, pruritus disappeared in the final week of pregnancy, a phenomenon that was not observed in patients with a genuine ICP.…”
mentioning
confidence: 99%
“…Glutathione S-transferase-alpha (GSTA, a specific marker of hepatocellular integrity) is significantly elevated in women with ICP, when compared with healthy pregnancies. Also, it is helpful in differentiating between ICP and pruritus gravidarum, a benign condition with no elevation of fetal risk [110]. Serum gamma-glutamyl transpeptidase (GGT) and 5 0 -nucleotidase activity are normal or only mildly increased.…”
Section: Clinical Presentation and Diagnostic Evaluationmentioning
confidence: 98%